Pengenalan Bahasa Bali menggunakan Media Gambar pada Anak Usia Dini - Wirani, Ida Ayu Sukma; Paramarta, I Ketut; Rai, Ida Bagus; Paryatna, Ida Bagus Made Ludy (UPI, 2019)
From the results of preliminary observations made at the Banjar Kindergarten, found problems regarding learning of the Balinese language at the Banjar Kindergarten and the availability of instructional media in class, to support the learning process is less supportive. One of the solutions offered is to conduct Balinese language learning training with drawing media at PAUD Teachers in Banjar Kindergarten. Based on the training that has been carried out, it can be concluded that the implementation of Balinese language learning training with drawing media for PAUD teachers in Banjar Kindergarten is going well and smoothly and has achieved the targets set previously. In addition, the teacher's response to the implementation of Balinese language learning training with drawing media on the teachers was very good, namely the teachers were very enthusiastic because they were seen to be very helpful in supporting Balinese language learning in PAUD.Â AbstrakDari hasil observasi awal yang di lakukan di TK Negeri Banjar, ditemukan permasalahan mengenai pembelajaran bahasa Bali di TK negeri Banjar dan ketersediaan media pelajaran di kelas, untuk mendukung proses pembelajaran kurang mendukung. Salah satu solusi yang ditawarkan adalah dengan mengadakan pelatihan pembelajaran bahasa Bali dengan media gambar Pada Guru-Guru PAUD di TK Negeri Banjar. Berdasarkan pada pelatihan yang telah dilakukan dapat disimpulkan bahwa pelaksanaan pelatihan pembelajaran bahasa Bali dengan media gambar pada guru-guru PAUD di TK Negeri Banjar berjalan dengan baik dan lancar serta telah mencapai target yang telah ditetapkan sebelumnya. Selain itu, respon guru-guru terhadap pelaksanaan pelatihan pembelajaran bahasa Bali dengan media gambar pada guru-guru sangat baik, yaitu guru-guru sangat antusias karena dipandang sangat membantu dalam menunjang pembelajaran bahasa Bali di PAUD.